EFFECTS OF Rosmarinus officinalis L. AQUEOUS EXTRACT ON ACUTE INFLAMMATION (Sciences & Technologie. C, Biotechnologies, 2015)
In this study, Rosmarinus officinalis L. aqueous extract was evaluated for anti-inflammatory activity by using the model of Carrageenan-induced rat paw oedema. Two doses of the aqueous extract (1500 mg/Kg and 3000 mg/Kg) were given orally by gavage technique, and then carrageenan was injected into the right hind paw of the rat. The extract, which was found rich in phenolic content (196.63 ± 3.09 mg GAE/ g E) and flavonoids (2.22 ± 0.09 mg RE/ g E), has shown a good inhibitory action (44.62 % in the third hour for the higher dose. *: p < 0.1) and close to that of aspirin that was used as a standard (31.87 % in the third hour for 200 mg/Kg aspirin.**: p < 0.05). The same effect was observed macroscopically on the gastric ulcer for both substances. However, the tissue alterations of the stomach were different at the histological study.